Underlying core-shell colloidal nanostructure for Beta zeolite membrane formation - Singh, Puyam S.; Aswal, Vinod K.; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2021)
Optimal design of Beta zeolite membrane of a three-dimensional 12-ring interconnected channel system can be vital for environmentally sustainable industrial separation application. A faster route of crystal growth from colloidal solution resulted to formation of poly (nanocrystalline) zeolite Beta membrane. The present SANS study probed the underlying functional diversity of core-shell precursor nanoparticle depending on form and structure factor towards the crystal growth for Beta membrane formation. The data clearly distinguished nanoscale structural arrangements of the synthesis solution before the hydrothermal heat treatment, during the induction and nucleation periods. Initially, shells consisting of organic template, reactive Al species and other dissolved ions surrounded the colloidal silica nanoparticles. Some of the silica cores sizes reduced while the shell thicknesses increased resulting to a heterogeneous colloidal solution system consisting of particles of different core-shell dimensions. The evolution of extra-small core and extra-large shell in the heterogeneous system may be nucleating particles as confirmed by XRD pattern corresponding of zeolite Beta. Deposition of such nucleating particles over the support might led to the formation of Beta zeolite membrane. The SANS profile of the solutions further showed that the nucleating particles were more readily deposited over the zeolite-seeded support than the non-seeded support.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Beta zeolite; Membrane; Nanoscale scattering; Nucleation; Precursor nanoparticle